Preservasi Digital di Sektor E-Government: Sebuah Kajian Literatur - Nurhayati, Lutfhi; Nur Pramudyo, Gani (Arsip Nasional Republik Indonesia, 2024)
E-government is a government administration system based on information and communication technology to facilitate communication and business transactions with various parties. Digital archives produced in e-government activities are vulnerable to damage due to threats such as viruses or cyberattacks. Therefore, digital preservation is needed in an effort to mitigate damage to digital archives in the e-government sector. This study aims to review issues in digital preservation practices in the e-government sector as well as provide recommendations for tools for digital preservation. The research method uses a qualitative approach by conducting an in-depth literature review. The results of this study reveal that the issues in digital preservation practices in the e-government sector are the lack of government support, the absence of policies regarding digital preservation, the lack of human resource capabilities, and the need for stakeholder participation and collaboration. The European Archival Records and Knowledge Preservation (E ARK) Project is recommended as a tool for digital preservation practices for archivists in the public sector.